Jean Tirole and Economic Science New Identity (2021)
In Economics for the Common Good, Jean Tirole sets a turning point in the way of conceiving the problems and methods used in economics. This article attempts to show that these components define a new identity for economic science, but without economic theory. To this end, Tirole's position according to which economics must be relocated within the social and human sciences is refuted. Consequently, this article contributes to reflection on the analytical scope of the new economic science and the meaning of what economists do nowadays.